Trace metal metabolism in plants - Andresen, Elisa; Peiter, Edgar; Küpper, Hendrik (Journal of experimental botany, 2018)
Many trace metals are essential micronutrients, but also potent toxins. Due to natural and anthropogenic causes, vastly different trace metal concentrations occur in various habitats, ranging from deficient to toxic levels. Therefore, one focus of plant research is on the response to trace metals in terms of uptake, transport, sequestration, speciation, physiological use, deficiency, toxicity, and detoxification. In this review, we cover most of these aspects for the essential micronutrients copper, iron, manganese, molybdenum, nickel, and zinc to provide a broader overview than found in other recent reviews, to cross-link aspects of knowledge in this very active research field that are often seen in a separated way. For example, individual processes of metal usage, deficiency, or toxicity often were not mechanistically interconnected. Therefore, this review also aims to stimulate the communication of researchers following different approaches, such as gene expression analysis, biochemistry, or biophysics of metalloproteins. Furthermore, we highlight recent insights, emphasizing data obtained under physiologically and environmentally relevant conditions.
Keywords: Plants; stopové prvky; kovy; Metals; rostliny; Trace Elements